Kaleidoscope of Inclusion: Mapping Music Learning Methods through the Lens of Contemporary Early Childhood Education Literature - Anggraeni, Santi Nisfi; Kurniawati, Leli (Universitas Pendidikan Ganesha, 2024)
The use of music learning methods in inclusive schools is considered as an innovative way to create an inclusive environment that stimulates children's holistic development. Even so, not many are aware of the urgency of music as a tool to achieve this inclusion, so a more in-depth study is needed. This study aims to analyze the role of music learning methods in inclusive early childhood education (ECE) in the contemporary era. Using a Systematic Literature Review (SLR) approach, this research aims to collect, review and analyze literature related to the use of music learning methods in inclusive ECE. Data collection techniques involve conducting a structured and comprehensive search on trusted databases. The data analysis process involved selecting literature based on inclusion and exclusion criteria, considering the relevance of articles and the necessary information. The results of the literature analysis found that music learning methods play an important role in creating an inclusive environment that stimulates early childhood participation and development. Music can open doors of communication, increase social interaction, and stimulate the creativity of inclusive children.